Mediation at School in Lithuania (Case Study) - Čiuladienė, Gražina (Pedagogika, 2018)
Schools implement peer mediation programs in order to fulfill the need for better conflict management among school students. It has been revealed that teaching students to be peacemakers is a very valuable competence benefiting them throughout their lives. Mediation is not used and even known conflict resolution strategy in Lithuania’s schools. Therefore, taking into account the lack of research on school based conflicts this research sets as its object conflict resolution education. It is inspired with the project idea “Mediation at schools” initiated by organization “Save the Children Lithuania” aiming to introduce the innovation – peer mediation as conflict management tool – at Lithuania’s schools. The research was conducted in one secondary school located in Vilnius, the capital of country. The purpose of the study was to evaluate the experience of pupils attending the peer mediation training (8 h) and mediators’ activities organized at school for a period of two months. The study revealed that pupils more often notice conflicts of others than to confess that they have a conflict themselves. When having a conflict with peers pupils are inclined to apply combat or collaboration strategy. 25 percent of the 7th grade pupils would like to become peer mediator. When generalising the findings, it can be concluded that mediation training and activities at schools were evaluated as successul. The challenge is to have positive attitude of peer mediation not only of those participated but as well of all school community members (authorities, teachers, parents, pupils) in order the method to be implemeted for a long period.